Continous, non-invasive monitoring of oxygen consumption in a parallelized microfluidic in vitro system provides novel insight into the response to nutrients and drugs of primary human hepatocytes - Marius Busche; Dominik Rabl; Jan Fischer; Christian Schmees; Torsten Mayr; Rolf Gebhardt; Martin Stelzle (EXCLI Journal : Experimental and Clinical Sciences, 2022)
Oxygen plays a fundamental role in cellular energy metabolism, differentiation and cell biology in general. Consequently, in vitro oxygen sensing can be used to assess cell vitality and detect specific mechanisms of toxicity. In 2D in vitro models currently used, the oxygen supply provided by diffusion is generally too low, especially for cells having a high oxygen demand. In organ-on-chip systems, a more physiologic oxygen supply can be generated by establishing unidirectional perfusion. We established oxygen sensors in an easy-to-use and parallelized organ-on-chip system. We demonstrated the applicability of this system by analyzing the influence of fructose (40 mM, 80 mM), ammonium chloride (100 mM) and Na-diclofenac (50 µM, 150 µM, 450 µM, 1500 µM) on primary human hepatocytes (PHH). Fructose treatment for two hours showed an immediate drop of oxygen consumption (OC) with subsequent increase to nearly initial levels. Treatment with 80 mM glucose, 20 mM lactate or 20 mM glycerol did not result in any changes in OC which demonstrates a specific effect of fructose. Application of ammonium chloride for two hours did not show any immediate effects on OC, but qualitatively changed the cellular response to FCCP treatment. Na-diclofenac treatment for 24 hours led to a decrease of the maximal respiration and reserve capacity. We also demonstrated the stability of our system by repeatedly treating cells with 40 mM fructose, which led to similar cell responses on the same day as well as on subsequent days. In conclusion, our system enables in depth analysis of cellular respiration after substrate treatment in an unidirectional perfused organ-on-chip system.